Comparison of Ultrasound and Motoyama Formula for Estimation of Endotracheal Tube Diameter in Pediatric Patients - Alam, Tasneem; Qureshi, Sajjad; Ali, Chaudhry Amjad; Hussain, Akhtar; Majeed, Kaukab; Qarni, Awais (Pakistan Armed Forces Medical Journal, 2024)
Objective: To assess the comparative effectiveness of Ultrasound and Motoyama formula for the calculation of endotracheal tube diameter in pediatric patients. Study Design: Quasi-experimental study Place and Duration of Study: The study was carried out at Department of Anesthesia Combined Military Hospital Quetta, Pakistan from May-Nov 2022. Methodology: The quasi experimental study was carried out at Anesthesia Department of Combined Military hospital Quetta from May to Nov 2022. A sample size of 40 patients was calculated with the aid of WHO sample size calculator. The patients were then divided into two equal groups of 20 patients each. Twenty patients were placed in group-U in which internal diameter of cuffed endotracheal tube was estimated through ultrasonography whereas 20 patients were placed in group-M in which age related Motoyama formula was used as guide to calculate the internal diameter of cuffed endotracheal tube. The intubation attempt was considered successful if tube was passed in first attempt. Statistical Package of Social Science (SPSS) version 26.0 was used to analyze and interpret data. Results: Both groups were similar in distribution of gender and ASA status. The intubation was successful in first attempt in 19(95%) of group-U patients while only 1(5%) patient had unsuccessful intubation at first attempt. While in group-M patients 13(65%) had successful intubation in first attempt and 7(35%) patients were not intubated at first attempt which showed that the ultrasound guided calculation of tube diameter was superior (p value <0.02). Conclusion: The ultrasonographic estimation of endotracheal tube diameter is more reliable as